Prevalence of and risk factors for trachoma in Kwara state, Nigeria: Results of eight population-based surveys from the Global Trachoma Mapping Project. (28th December 2018) - Alada, Joel J.; Mpyet, Caleb; Florea, Victor V.; Boisson, Sophie; Willis, Rebecca; Muhammad, Nasiru; Bakhtiari, Ana; Adamu, Mohammed D.; Pavluck, Alexandre L.; Umar, Murtala M.; Isiyaku, Sunday; William, Adamani; et al.
ABSTRACT: Purpose : To determine the prevalence of and risk factors for trachoma in selected local government areas (LGAs) of Kwara State, Nigeria. Methodology : Population-based cross-sectional surveys were conducted in eight LGAs of Kwara State using Global Trachoma Mapping Project (GTMP) protocols. In each LGA, 25 villages were selected using probability-proportional-to-size sampling; 25 households were selected from each village using compact segment sampling. All residents of selected households aged ≥1 year were examined by GTMP-certified graders for trachomatous inflammation—follicular (TF) and trichiasis using the simplified trachoma grading scheme. Water, sanitation, and hygiene (WASH) data were also collected. Results : A total of 28, 506 residents were enumerated in 4769 households across the eight LGAs. TF prevalence in children aged 1–9 years ranged from 0.2% (95% CI 0.0–0.3%) to 1.3% (95% CI 0.7–2.1%), while trichiasis prevalence in persons ≥15 years was <0.2% in each LGA. Access to improved water source was the lowest in Edu (62%), while access to improved sanitation facilities was the lowest in Asa (6%) and the highest in Ilorin East (64%). Children aged 1–4 years had 0.63 (95% CI 0.40–0.99) times lower odds of having TF compared to children aged 5–9 years. Children in households with ≥5 resident 1–9-year-old children had 1.63 (95% CI 1.02–2.60) times greater odds of having TF compared to those in households with <5 resident children. Conclusion : Trachoma is not a public health problem in Kwara State. Provision of adequate water and sanitation services should be a priority here, as a foundation for the health of the population.